Biokinetic analysis of the stages of weight lifting and its relationship to the level of achievement for elite female players in Iraq (College of Basic Education Research Journal, 2025)
The research aims to :  1-Identifying some biokinetic variables for elite female players in Iraq with the effectiveness of pushing weight.  2-Studying the relationship between some biogenetic variables of elite players in Iraq with the effectiveness of pushing weight and the level of achievement .The study was conducted on a sample of (4) top players in the effectiveness of weightlifting participating in the Iraqi championships, and they are the elite participants. The researcher used video imaging with a high-speed camera (220 images / sec). By using the kinetic analysis program for the purpose of obtaining the required data, the researcher has used statistical means such as the mean, standard deviation, coefficient of variation and the simple correlation coefficient using the (spps) bag to process the data, and the results obtained by the researcher were discussed as follows:  1-The lack of horizontal distance negatively affected the achievement .  2-The resultant lack of distance had a negative impact on the achievement.  3-The height of the center of gravity of the body has an effect on achievement because it works to direct the body upwards .  4-The horizontal speed of the arm aiming for the pushing stage has a positive effect on the achievement.  5-The ability of the shooter to release the weight in a shorter time had a positive impact on achievement.The following recommendations were reached :  1-Emphasis on performing the glide stage correctly because it gains the body and weight at an initial speed to achieve a better achievement . 2-The need to pay attention to the angle of launch of the weight, because it is one of the factors affecting the projectile.  3-Emphasis on the technical performance on the mechanical basis, starting from the starting position in the throwing circle, passing through the glide, then the launching stage and throwing the tool as far as possible .